US Tobacco 21 is Paving the Way for a Tobacco Endgame - Samuel C J Kim (SAGE Publishing, 2021)
The battle against tobacco usage is being fought on all fronts. On December 19, 2019, a measure to raise the minimum age to buy tobacco products to 21 from 18 was passed by the United States Congress and signed by President Donald Trump. This instated banning the sale of all tobacco products and electronic cigarettes to anyone in the US under the age of 21. This follows the raising of the age to buy tobacco in California to 21 in 2016. According to the California Tobacco Control Program: in 2016, roughly 10% of high-school students were smoking cigarettes, but by 2018, only 2%. The percentage of retailers selling tobacco to underaged youth dropped dramatically. These data show that the CA Tobacco 21 law was effective in decreasing the obtainability and usage of tobacco by youth. We expect that US Tobacco 21 will be similarly effective in reducing tobacco use by youth leading to less tobacco addiction in the US.